The New Silk Road as the Pendulum Axis of History: China’s “Journey to the West” Opens a Range of Opportunities to Europe - Higueras, Georgina (Sinología hispánica. China Studies Review, 2019)
The pendulum of History leaves the West to return to the East, as in the times of Marco Polo. China has found in the resurrection of the Silk Road the instrument for a more inclusive global economic growth and that is also in line with the multipolar world that the government proposes. In just five years, The Belt and Road Initiative, as it is formally referred to, has made great strides in its revolutionary global connection plan and added new followers, despite of the swiftness of the Chinese’s ascent is scaring many countries, especially its neighbors. The purpose of this article is to analyze the misgivings of Europe and the range of opportunities that Beijing is offering to create together a model of sustainable development and address the major challenges that affect both: inequality, climate change and protectionist drift. The New Silk Road is a unique opportunity to bring closer the two extremes of Eurasia, which today, more than ever, need to understand each other.